2018
DOI: 10.1063/1.5009496
|View full text |Cite
|
Sign up to set email alerts
|

Dust-acoustic shock waves in a dusty plasma with non-thermal ions and super-thermal electrons

Abstract: The propagation of dust-acoustic shock waves (DASWs) in a collisionless unmagnetized dusty plasma (containing super-thermal electrons of two distinct temperatures, non-thermal ions, and a negatively charged viscous dust fluid) has been theoretically investigated by deriving and solving the nonlinear Burgers' equation. It has been observed that the viscous force acting on the dust fluid is a source of dissipation, and is responsible for the formation of DASWs, and that the basic features (viz., amplitude, polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…It is demonstrated that the dynamics of small but finite amplitude DA waves is regulated by a nonlinear equation of modified Korteweg-de Vries (mK-dV) type. The basic characteristics and propagation of dust-acoustic (DA) shock waves (DASHWs) [161] in self-gravitating dusty plasmas containing massive dust of opposite polarity, trapped ions, and Boltzmann electrons are explored in [370,371]. The reductive perturbation technique is applied to infer the standard modified Burgers equation (mBE).…”
Section: Regions Of Single Particle Confinementmentioning
confidence: 99%
“…It is demonstrated that the dynamics of small but finite amplitude DA waves is regulated by a nonlinear equation of modified Korteweg-de Vries (mK-dV) type. The basic characteristics and propagation of dust-acoustic (DA) shock waves (DASHWs) [161] in self-gravitating dusty plasmas containing massive dust of opposite polarity, trapped ions, and Boltzmann electrons are explored in [370,371]. The reductive perturbation technique is applied to infer the standard modified Burgers equation (mBE).…”
Section: Regions Of Single Particle Confinementmentioning
confidence: 99%
“…Sharma et al [21] have studied the Jeans instability and low frequency modes in dusty plasma, including non-thermal ions, Maxwellian electrons, dust polarization force and charge fluctuation. Considering superthermal electrons and non-thermal ions in dusty plasma, Emamuddin and Mamun [22] have examined dust acoustic shock waves. Furthermore, most of the studies mentioned above have been carried out for homogeneous dusty plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…T e , and α 4 = Z d n d0 /Z i n i0 . The normalized form of the number density of electron regarding the κ-distribution is represented as [21,22]…”
Section: Governing Equationsmentioning
confidence: 99%
“…These highly energetic particles are governed by super-thermal (κ)distribution [20], and the parameter κ in the κ-distribution presents the deviation of energetic particles from the thermally equilibrium state. The κ-distribution becomes Maxwellian distribution for large values of κ (i.e., κ → ∞) [21,22,23,24]. Emamuddin and Mamun [22] examined the dust-acoustic shock waves in a multi-component plasma medium having superthermal electrons, and found that the width of the shock profile decreases with the super-thermal effect of the electrons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation